Noncompaction of ventricular myocardium: A study of twelve patients - (:unkn) unknown (MOSBY, INC, 2002)
We report 12 patients with ventricular noncompaction who were echocardiographically identified at our institution since 1991. The mean age at presentation was 3.5 years. Five patients had isolated noncompaction. Three of them had subnormal left ventricular systolic function at presentation. Noncompaction was associated with complex congenital heart defect in 3 patients. Four patients had simple congenital heart defects: pulmonary stenosis, coarctation of aorta with aberrant origin of right subclavian artery, ventricular septal defect, and partial anomalous pulmonary venous return. The observed rhythm abnormalities were Wolff-Parkinson-White syndrome and paroxysmal supraventricular tachycardia, bigemini ventricular extrasystoles, and left bundle branch block. A transvenous pacemaker was implanted in a patient because of complete heart block. Noncompaction of the ventricular myocardium is rare. Our patients clearly represent the clinical and morphological spectrum of this disorder. Distinct morphological features can be diagnosed on 2-dimensional echocardiography.
Keywords: ADULTS